Pengaruh Pengembangan Karir, Kompensasi, dan Beban Kerja terhadap Turnover Intention Karyawan Generasi Z di Kota Mataram - I Gusti Ayu Prianingsih; Widia Febriana; Febria Nurmelia Marlina; Irwan Cahyadi; Ega Dwi Putri Marswandi (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The increasingly dynamic work environment has led to higher turnover intention, particularly among Generation Z employees. This generation grew up in the digital era and possesses different characteristics compared to previous generations, such as rapid adaptation to technology, preference for work flexibility, and high expectations regarding career development, compensation, and a comfortable work environment. Generation Z employees also tend to change jobs more easily when they perceive limited career growth opportunities, inadequate rewards, and excessive workloads. These conditions encourage companies to understand the factors influencing turnover intention in order to retain potential employees. This study aims to examine the influence of career development, compensation, and workload on turnover intention among Generation Z employees in Mataram. The study employed a quantitative approach involving 100 Generation Z employees from various organizations and companies. Data were collected through questionnaires and analyzed using SPSS, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that career development and workload have a positive and significant effect on turnover intention, while compensation has a negative and significant effect on turnover intention. Simultaneously, the three variables significantly affect turnover intention with a coefficient of determination value of 53.3%, while the remaining percentage is influenced by other factors outside this study.